Agricultural Lending : A How-To Guide - International Finance Corporation (International Finance Corporation, Hanoi, 2017)
This toolkit introduces and explains step by step the key elements of success for FIs to expand financial services to farmers. The content was developed around IFC’s global experience in assisting FIs with the development and implementation of agricultural finance products. The benefits of this work are synthesized in this guide, along with knowledge and expertise of best practices among both IFC clients and others. The guide includes advice on each step involved and tips on how to address the complex challenges that might arise during product development process. The guide has seven chief components: introduction to agricultural finance, the product development process, product development phase one – preparation, product development phase two – market research, product development phase three – pilot design, product development phase four - pilot testing and monitoring, and product development phase five – product launch and rollout.